Fabrication and characterization of thiol-triacrylate polymer via Michael addition reaction for biomedical applications. (25th October 2018) - Forghani, Anoosha; Garber, Leah; Chen, Cong; Tavangarian, Fariborz; Tighe, Timothy B; Devireddy, Ram; Pojman, John A; Hayes, Daniel
Abstract: Thiol-acrylate polymers have therapeutic potential as biocompatible scaffolds for bone tissue regeneration. Synthesis of a novel cyto-compatible and biodegradable polymer composed of trimethylolpropane ethoxylate triacrylate-trimethylolpropane tris (3-mercaptopropionate) (TMPeTA-TMPTMP) using a simple amine-catalyzed Michael addition reaction is reported in this study. This study explores the impact of molecular weight and crosslink density on the cyto-compatibility of human adipose derived mesenchymal stem cells. Eight groups were prepared with two different average molecular weights of trimethylolpropane ethoxylate triacrylate (TMPeTA 692 and 912) and four different concentrations of diethylamine (DEA) as catalyst. The materials were physically characterized by mechanical testing, wettability, mass loss, protein adsorption and surface topography. Cyto-compatibility of the polymeric substrates was evaluated by LIVE/DEAD staining ® and DNA content assay of cultured human adipose derived stem cells (hASCs) on the samples over over days. Surface topography studies revealed that TMPeTA (692) samples have island pattern features whereas TMPeTA (912) polymers showed pitted surfaces. Water contact angle results showed a significant difference between TMPeTA (692) and TMPeTA (912) monomers with the same DEA concentration. Decreased protein adsorption was observed on TMPeTA (912) -16% DEA compared to other groups. Fluorescent microscopy also showed distinct hASCs attachment behavior between TMPeTA (692) and TMPeTA (912), which is due to their different surface topography, protein adsorption and wettability. Our finding suggested that this thiol-acrylate based polymer is a versatile, cyto-compatible material for tissue engineering applications with tunable cell attachment property based on surface characteristics.